New entry, strategic diversity and efficiency in soccer betting markets: the creation and suppression of arbitrage opportunities - Grant, Andrew; Oikonomidis, Anastasios; Bruce, Alistair C.; Johnson, Johnnie E.V. (Taylor & Francis, 2018)
We find that prices offered by competing bookmakers within the same quote-driven soccer (football) betting market provide arbitrage opportunities. However, the management practices of bookmakers prevent informed bettors exploiting these in practice. We identify two groups of bookmakers, ‘position-takers’ and ‘book-balancers.’ Position-takers alter their odds infrequently, while actively restricting informed traders. Book-balancers actively manage inventory by adjusting odds, and place few restrictions on their customers. We identify 545 arbitrage portfolios, and find that around 50% would require a bet on the favourite at the position-taking bookmaker. The management practices of position-takers generally prevent these opportunities being exploited in practice.